E Effectiveness of Using Wordless Picture Books to Develop Creative Thinking Abilities in Elementary School Students - Nina Nurhasanah; Uswatun Hasanah; Iva Sarifah; Maey Muliyati; Insyirah Meizaluna A.P (Universitas Pendidikan Ganesha, 2026)
The limited variety of innovative teaching materials and the low level of students’ creative thinking skills remain key challenges in Pancasila Education. The use of wordless picture books is considered an alternative teaching material that can foster creativity through visual illustrations that provide space for imagination and open interpretation. This study aims to examine the effectiveness of wordless picture books in improving students’ creative thinking skills. The research employed a quantitative method with a quasi-experimental design using a one group pretest posttest approach. The subjects of the study consisted of 21 elementary school students. Data were collected using a creative thinking skills test and a questionnaire, with instruments in the form of essay questions based on creative thinking indicators and a questionnaire on students’ responses to the use of the teaching material. Data analysis was conducted using descriptive quantitative techniques and N-Gain analysis to measure improvement. The results indicate that the use of wordless picture books is effective in enhancing students’ creative thinking skills, as reflected in improvements in fluency, flexibility, originality, and elaboration. The study concludes that wordless picture books are an innovative teaching material capable of creating more active, meaningful, and student centered learning. The findings imply that visual illustration-based teaching materials can serve as a strategic alternative for developing creative thinking skills while supporting contextual learning relevant to students’ daily lives.